Bacterial Proteins and Peptides as Potential Anticancer Agents: A Novel Search for Protein-based Therapeutics - Pyla, Mahitha; Kankipati, Sanjana; Sumithra, Bapatla; Mishra, Piyush Kumar; Mishra, Bishwambhar; Mandal, Sanjeeb Kumar; Panda, Jibanjyoti; Chopra, Hitesh; Avula, Satya Kumar; Attia, Mohamed Salah; Mohanta, Yugal Kishore; Kamal, Mohammad Amjad (Current Medicinal Chemistry, 2025)
Tumor diseases remain among the world's primary causes of death despite substantial advances in cancer diagnosis and treatment. The adverse chemotherapy problems and sensitivity towards drugs for some cancer types are among the most promising challenges in modern treatment. Finding new anti-cancer agents and drugs is, therefore, essential. A significant class of biologically active substances and prospective medications against cancer is comprised of bacterial proteins and peptides. Among these bacterial peptides, some of them, such as anti-cancer antibiotics and many toxins like diphtheria are widely being used in the treatment of cancer. In contrast, the remaining bacterial peptides are either in clinical trials or under research in vitro studies. This study includes the most recent information on the characteristics and mechanism of action of the bacterial peptides that have anti-cancer activities, some of which are now being employed in cancer therapy while some are still undergoing research.
Keywords: anti-cancer antibiotics